2015
DOI: 10.15547/tjs.2015.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of TNF-alpha and spirometric parameters in workers exposed to inorganic dust

Abstract: АBSTRACTInhalation of inorganic particles results in activation of the alveolar macrophages with subsequent release of inflammatory cytokines and fibroblast proliferation. PURPOSE of this work was to analyze the serum levels of TNF-α and basic spirometric parameters in clinically healthy workers exposed to inorganic dust of different chemical composition. METHODS: the studied workers were divided into two groups depending on the characteristics of the dust: Group A (29 workers) exposed to dust from moulding ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Consistent with our findings, Prakova et al reported serum neopterin levels to be high in miners exposed to asbestos and coal dust. 41 Increased neopterin levels have also been reported in miners exposed to bauxite dust, 42 while another study has suggested that levels are increased in tuberculosis which may be associated with the stimulation of cellular immune response. 43 Workers exposed to dust containing free crystalline silicon dioxide were found to have higher neopterin levels compared to the control group.…”
Section: Discussionmentioning
confidence: 97%
“…Consistent with our findings, Prakova et al reported serum neopterin levels to be high in miners exposed to asbestos and coal dust. 41 Increased neopterin levels have also been reported in miners exposed to bauxite dust, 42 while another study has suggested that levels are increased in tuberculosis which may be associated with the stimulation of cellular immune response. 43 Workers exposed to dust containing free crystalline silicon dioxide were found to have higher neopterin levels compared to the control group.…”
Section: Discussionmentioning
confidence: 97%
“…Immune cells interact with antigens which lead to the release of chemical substances called cytokines that affect other cells and coordinate appropriate immune responses. Cytokines include interleukins, interferons, growth factors, monokines, and lymphokines (Prakova et al, 2015). Measurement of soluble cytokines in vivo and in vitro is becoming increasingly important in studying and controlling pulmonary diseases (Chowdhury et al, 2009).…”
Section: Introductionmentioning
confidence: 99%